The Ganzflicker experience: High probability of seeing vivid and complex pseudo-hallucinations with imagery but not aphantasia. (August 2021) - Königsmark, Varg T.; Bergmann, Johanna; Reeder, Reshanne R.
Abstract: There are considerable individual differences in visual mental imagery ability across the general population, including a "blind mind's eye", or aphantasia. Recent studies have shown that imagery is linked to differences in perception in the healthy population, and clinical work has found a connection between imagery and hallucinatory experiences in neurological disorders. However, whether imagery ability is associated with anomalous perception–including hallucinations–in the general population remains unclear. In the current study, we explored the relationship between imagery ability and the anomalous perception of pseudo-hallucinations (PH) using rhythmic flicker stimulation ("Ganzflicker"). Specifically, we investigated whether the ability to generate voluntary imagery is associated with susceptibility to flicker-induced PH. We additionally explored individual differences in observed features of PH. We recruited a sample of people with aphantasia (aphants) and imagery (imagers) to view a constant red-and-black flicker for approximately 10 min. We found that imagers were more susceptible to PH, and saw more complex and vivid PH, compared to aphants. This study provides the first evidence that the ability to generate visual imagery increases the likelihood of experiencing complex and vivid anomalous percepts.